Block Disabling Characterization and Improvements in CMPs Operating at Ultra-low Voltages - Ferrerón, Alexandra; Suárez-Gracia, Darío; Alastruey-Benedé, Jesús; Monreal, Teresa; Viñals, Víctor (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2014)
Power density has become the limiting factor in technology scaling as power budget restricts the amount of hardware that can be active at the same time. Reducing supply voltage to ultra-low voltage ranges close to the threshold region has the promise of great energy savings. However, the potential savings of voltage scaling are limited by the correct operation of SRAM cells, which is not guaranteed below Vddmin, the minimum voltage in which cache structures operate reliably. Understanding the effects of operating below Vddmin requires complex modelling, so we introduce an updated probability failure model of SRAM cells at 22nm and explore the reliability impact of lowering the chip voltage supply below Vddmin in shared memory coherent chip-multiprocessors (CMP) running a variety of parallel workloads. A micro architectural technique to cope with cache reliability at ultra-low voltages is block disabling, however, in many cases, the savings in on-chip caches do not compensate for the consumption in the rest of the system, as the consumption increase of the off-chip memory may offset the on-chip gain. We make the case that existing coherence mechanisms can provide the substrate to improve energy savings with block disabling and propose two low-complexity techniques. Taking the best of both techniques we can scale voltage below Vddmin and reduce system energy up to 39%, and system energy-delay up to 10%. Besides, by lowering the CMP consumption in a power constrained scenario, we could activate offline cores, reaching a potential speedup between 3.7 and 4.4.